Structural control of high-rise buildings subjected to multi-hazard excitations using inerter-based vibration absorbers. (1st September 2022) - Qiao, Haoshuai; Huang, Peng; De Domenico, Dario; Wang, Qinhua
Highlights: Mechanism of multiple-mode control of inerter-based vibration absorbers (IVAs). Comparison of the generalized MDOF and SDOF model. Guidance for parametric design and performance evaluation of IVAs. Optimal design and performance evaluation of IVAs under multi-hazard excitations. Abstract: High-rise buildings located in strong wind and earthquake-prone regions are exposed to multiple hazards that must be properly considered to prevent considerable socio-economic losses. In the present study, the Tuned Mass Damper-Inerter (TMDI) is adopted for the structural control of high-rise buildings under wind and earthquake excitations by exploiting its inherent multiple-mode control effects. A generalized multi-degree-of-freedom (MDOF) model of TMDI-controlled structure is established first and compared with the commonly-adopted generalized single-degree-of-freedom (SDOF) model. Analytical investigation on the multiple-mode control effects of TMDI demonstrates that the damping effects weighted by mode coordinate differences at two terminals of TMDI are mainly responsible for its multiple-mode control effects. Based on a real high-rise building project, analysis errors induced by the generalized SDOF model against the more accurate generalized MDOF model are quantified by a comprehensive Monte Carlo simulation, which suggests the necessity of adopting numerical search for parametric design of TMDI under most circumstances. Therefore, the parameters of TMDI and its two competitors, i.e., Multi-Tuned Mass Damper (MTMD) and Multi-Tuned Mass Damper-Inerter (MTMDI), are optimized using a genetic algorithm, assuming both wind- and earthquake-induced responses as performance objectives. Time and frequency domain analyses demonstrate the efficiency of utilizing the multiple-mode control effects of a single TMDI for multi-hazard design. The trend of the equivalent damping ratio of TMDI-controlled structure on an arbitrary mode is analyzed to identify the design parameters affecting most the TMDI multiple-mode control effect at last.